THE EFFECT OF DEMOCRATIC LEADERSHIP STYLE IN IMPROVING THE QUALITY HIGHER EDUCATION OF PGRI - BASED MANAGEMENT IN EAST JAVA - Abd Syakur; Sabar Narimo; Harun Joko Prayitno (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
The goal of this study was to determine the effect of democratic leadership on the quality of processing higher education institutions (PT) on PGRI-based in East Java. This study employed a correlational quantitative research approach. The population of this study included all leaders of Private Higher Education (PTS) in the LLDIKTI VII East Java area, with a total of 60 samples chosen at random. With a 95 percent confidence level, the maximum error rate considered in this study was 5%. Based on the SPSS 26 test results, it was known that the instrument of democratic leadership style (X) and improving the quality of PT management (Y) was declared 'valid' with a calculated r value (X) of 0.758 and (Y) of 0.798 (with a r table value of 0.308). Cronbach Alpha values of 0.811 (X) and 0.856 (Y) indicated high reliability. The results of hypothesis testing (I) obtained the regression equation, namely Y = -2.765 + 0.225X, and the results of hypothesis testing (2) obtained t arithmetic (1.341) > t table (1.256) and a significance value of 0.02 > 0.05, so it can be concluded that Ha is accepted, which means that the democratic leadership style variable has a significant influence (there is still a low category influence relationship) on the quality of management of PGRI-based universities in East Java.